2010
DOI: 10.1095/biolreprod.110.085233
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Equine Endometrium at Days 8 and 12 of Pregnancy1

Abstract: Establishment and maintenance of pregnancy in equids is only partially understood. To provide new insights into early events of this process, we performed a systematic analysis of transcriptome changes in the endometrium at Days 8 and 12 of pregnancy. Endometrial biopsy samples from pregnant and nonpregnant stages were taken from the same mares. Composition of the collected biopsy samples was analyzed using quantitative stereological techniques to determine proportions of surface and glandular epithelium and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
82
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 106 publications
11
82
1
2
Order By: Relevance
“…The regulation of the uterine transcriptome during the preimplantation phase has been intensively studied in several species (sheep (73), bovine (74,75), horse (21,76), and pig (77)(78)(79)) and the proteome of uterine fluid during the early stages of pregnancy was analyzed in cattle and sheep (80 -82). Several proteins we found more abundant in the uterine luminal fluid during the luteal phase were also described as uterine markers of early pregnancy with an increased production in the presence of an embryo.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of the uterine transcriptome during the preimplantation phase has been intensively studied in several species (sheep (73), bovine (74,75), horse (21,76), and pig (77)(78)(79)) and the proteome of uterine fluid during the early stages of pregnancy was analyzed in cattle and sheep (80 -82). Several proteins we found more abundant in the uterine luminal fluid during the luteal phase were also described as uterine markers of early pregnancy with an increased production in the presence of an embryo.…”
Section: Discussionmentioning
confidence: 99%
“…In term human placental tissues, CRYAB was visibly observed in the stromal cells of the placental villi (Mineva et al 2008). In equine endometrium, CRYAB was detected on days 12 and 13.5 of pregnancy (Klein et al 2010, Merkl et al 2010. During the menstrual cycle, CRYAB was expressed in human and baboon endometrium and also upregulated during the window of implantation (Gruidl et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…These include ischemic tolerance in the brain or heart [40,41], regulation of cellular metabolism by targeting mitochondria [42,43] and association with angiogenesis in endothelial cells [44]. Quite recently, the presence of endometrial STC1 in pregnant mares was reported [45]. Although receptors possibly located on the conceptus or functions of endometrial STC1 have not been established in the mare, STC1 could have a role in regulating embryonic calcium and/or phosphorus concentrations at a time in which the conceptus is not supported by a functional placenta.…”
mentioning
confidence: 99%